The Urgency of Changing the Status of Indonesian Seamen from Migrant Workers to Seafarer With Permanent Legal Forcement Through the Influence of Good Corporate Governance Policies on the Welfare of Seafarer - Kemala Atmojo; Umar Aris; Marjan Miharja; Hartanto Hartanto; Maltus J. Kapistrano; Leonard Immanuel Parlindungan Siregar (Borong Newinera Publisher, 2023)
Despite the status of Sailors or Seamen Working as Members of Ships (Seafarers) as a group it seems to have been placed vaguely among the legal terms used in the recent discourse on international labor migration and circulation which is in stark contrast to the conceptual location of Seafarers especially for those working in denationalized international maritime space. The framework in this study outlines material regarding the flow of writing in describing, analyzing, elaborating, and finding answers to legal issues regarding the urgency of changing the status of Indonesian seamen from Migrant Workers to Seafarers with permanent legal force which in other words can be interpreted as the influence of good corporate governance on the welfare of the Seafarer. The purpose of the study was to determine the direct and indirect influence of the urgency of changing the status of Indonesian Seamen from Migrant Workers to Seafarer with permanent legal force through the influence of Good Corporate Governance Policies on the Welfare of the Seafarer. The design used in this research is associative with survey method. The population in this study was the Seafarer. The sampling technique used in this study was purposive sampling with a total sample of 66 respondents. The data collection technique uses a questionnaire that has been tested for validity and reliability. This research uses path analysis method with Smart Partial Least Square software ver. 3. The results of this study indicate that the faienesshas a direct positive effect on the Seafarer Welfare, the transparancyhas a direct positive effect on the Seafarer Welfare, the Accountability has a direct positive effect on Seafarer Welfare and the Responsibility has a direct positive effect on the Seafarer Welfare.